Assessing forest products usage and local residents' perception of environmental changes in peri-urban and rural mangroves of Cameroon, Central Africa - Nfotabong-Atheull, Adolphe (BioMed Central, 2011)
BACKGROUND: Deforestation is one of the most ubiquitous forms of land degradation worldwide. Although remote sensing and aerial photographs can supply valuable information on land/use cover changes, they may not regularly be available for some tropical coasts (e.g., Cameroon estuary) where cloud cover is frequent. With respect to mangroves, researchers are now employing local knowledge as an alternative means of understanding forest disturbances. This paper was primarily aimed at assessing the mangrove forest products usage, along with the local people's perceptions on environmental changes, between Littoral (Cameroon estuary) and Southern (mouth of the Nyong River and Mpalla village) regions of Cameroon. METHODS: The data from both locations were obtained through conducting household interviews and field observations. RESULTS: In the Cameroon estuary (Littoral region), 69.23% of respondents (mostly elders) could distinguish two to four mangrove plants, whereas the informants (65.45%) in the mouth of the Nyong River and Mpalla village (mostly young people interviewed from the Southern region) are familiar with only one or two commonly found mangroves. Also, more respondents from the Cameroon estuary are depending on mangroves for fuelwood (Rhizophora spp.) and housing (Rhizophora spp., Avicennia germinans (L.) Stearn and Nypa fruticans (Thumb.) Wurmb.) purposes, in contrast to Nyong River mouth and Mpalla village. Although local people perceived wood extraction as a greater disruptive factor, there are several causes for mangrove depletion in the Cameroon estuary. Among others, over-harvesting, clear-felled corridors, sand extraction and housing were found important. Furthermore, a decline in mangrove fauna composition (in terms of fishery products) was recorded in the Littoral as well as Southern regions. However, the causes of such perceived negative changes were not similar in both cases. CONCLUSIONS: Findings of this study highlight the need to improve sustainable management of the mangrove ecosystems through afforestation (in large impacted areas), selective removal of senescent tree stems and branches (in little damage stands), regulating sand extraction and housing activities, and creating awareness and law enforcement.